Prevalence of Chronic Pain, Impact on Daily Life, and Treatment Practices in India. Issue 2 (4th December 2013) - Dureja, Gur Prasad; Jain, Paramanand N.; Shetty, Naresh; Mandal, Shyama Prasad; Prabhoo, Ram; Joshi, Muralidhar; Goswami, Subrata; Natarajan, Karthic Babu; Iyer, Rajagopalan; Tanna, D. D.; Ghosh, Pahari; Saxena, Ashok; et al.
Abstract Objective Chronic pain is of concern to health professionals, patients, society, and negatively impacts quality of life (QoL). The present epidemiologic study identified point prevalence of chronic pain in India, impact on individual's QoL, unveiling current pain treatment practices, and levels of satisfaction with treatment. Methods This epidemiological telephonic survey consisted of two questionnaires: screening questionnaire that assessed prevalence of pain, its frequency during the past week, intensity during last episode, sites of pain, and main causes, and in‐depth questionnaire that evaluated demography, frequency, duration, and intensity of pain; impact of pain on QoL; respondent's perception regarding the attitude of their family, friends, and doctors toward their pain. Results A total of 5004 respondents were included from eight cities across India. The overall point prevalence of chronic pain was 13%, and the mean intensity of pain on NRS scale was 6.93. Respondents with chronic moderate and chronic severe pain were 37% and 63%, respectively. Pain in knees (32%), legs (28%), and joints (22%) was most prevalent. Respondents with chronic pain were no longer able to exercise, sleep, maintain relationships with friends and family, and maintain an independent lifestyle. About 32% of patients lost ≥4 hours of work in the past 3 months. Majority (68%) of respondents were treated for pain with over the counter (OTC) drugs, and most were taking NSAIDs (95%). Conclusion A significant population of India suffers from chronic pain, and their QoL is affected leading to disability. A proportion of respondents receiving pain treatment were taking nonprescription medications with a majority of respondents on NSAIDs. A very few were consulting pain management specialists.